Micro, Small, and Medium Enterprises (MSMEs) Development Strategy: A Systematic Review of Global Practices and an Integrative Framework - Fatolosa Hulu; Rahmi Fahmi (Journal of Research in Social Science and Humanities, 2025)
This systematic review synthesizes the research on strategic interventions that foster the growth and sustainability of Micro, Small, and Medium Enterprises (MSMEs). By conducting a comprehensive analysis of twenty studies sourced from high-quality databases, we categorized the findings into nine strategic themes: Human Capital, Technology, Social Capital, Entrepreneurial Orientation, Financial Support and Accessibility, Market Strategy and Expansion, Organizational and Operational Efficiency, Innovation and Product Development, and Gender Equality and Empowerment. Our review highlights the critical role of integrating advanced HR analytics with organizational strategies, leveraging technology for operational efficiency, and fostering an entrepreneurial mindset to enhance dynamic capabilities and innovation within MSMEs. We also underscore the significance of financial accessibility, market expansion strategies, organizational efficiency, product innovation, and gender empowerment in cultivating a competitive edge. Despite the extensive strategies explored, we identified gaps, particularly the lack of empirical research assessing the direct impact of these strategies in different socio-economic contexts, especially within developing nations. Our findings call for targeted policy interventions and future research focused on implementing effective strategies, considering the unique challenges faced by MSMEs in an increasingly digital and globalized economy.